Digital transformation in human resource management and work experience on digital efficacy: The mediating role of the generational gap - Abd. Rasyid Syamsuri; Sharnuke Asrilsyak; Rezi Abdurrahman (Journal of Applied Business Administration, 2026)
This study aims to analyze the influence of digital transformation and work experience on employees' digital efficacy, considering the mediating role of the generational gap. The research was conducted at PT Besmindo Materi Sewatama, an energy-sector company currently implementing digitalization in its human resources management functions. Using a quantitative approach and the SEM-PLS 4 method, data were collected from 110 employees through a total sampling technique. The findings indicate that both digital transformation and work experience significantly influence digital efficacy. Among these, work experience emerged as the dominant factor shaping employees' confidence in using technology, while the generational gap did not exhibit a significant mediating effect. The novelty of this study lies in integrating the four variables into a single comprehensive structural model. These findings offer practical implications for organizations in designing cross-generational training strategies and HR management practices to support inclusive and sustainable digital transformation.